The split application of potassium influence the production, nutrients extraction, and quality of sweet potatoes - Correa, Carla Veronica [UNESP]; Sousa Gouveia, Aline Mendes de [UNESP]; Lima Lanna, Natalia de Brito [UNESP]; Barbosa Tavares, Ana Emilia [UNESP]; Mendonca, Veridiana Zocoler [UNESP]; Campos, Felipe Girotto [UNESP]; Silva, Janaina Oliveira [UNESP]; Inacio Cardoso, Antonio Ismael [UNESP]; Evangelista, Regina Marta [UNESP] (Taylor & Francis Inc, 2018)
The current study aimed to evaluate the effect of split application of potassium (K) fertilizer on the production and quality of sweet potatoes. Ten treatments were evaluated in factorial design (3 x 3 + 1): three doses of potassium (60, 90, and 120 kg K2O ha(-1)); three application types (100% applied at planting; 50% applied at planting and 50% was given as topdressing; 25% applied at planting and 75% was given as topdressing) and one control (without the application of K2O either at planting or topdressing). The experiment used a randomized complete block design and four repetitions. The following parameters were studied: root number; root fresh matter per plant; total dry matter; yield; total macronutrient extraction; sugar content of starch; and commercial starch. The production characteristics of the roots presented a significant interaction between the factors doses of potassium and application types (parcelaments). Finally, better results were obtained when potassium was applied 50% at planting and 50% as topdressing.
Keywords: Ipomoea batatas L.; macronutrients; nutrition; post-harvest; yield